Students’ Perception towards Teacher’s Code-switching in EFL Clasroom: Exploring Pedagogical Functions - Wibowo, Fanny; Rahmawati, Maya; Kamil, Acep Bahrum (Edumaspul: Jurnal Pendidikan, 2021)
Code-switching is an inevitable phenomenon that often happens inside a foreign or second English classroom. However, this phenomenon is often treated like the elephant in the room: the teacher recognizes its presence but is never really aware of it. While many studies regarding code-switching topics in EFL classrooms only focus on analyzing the type of teacher's code-switching. This study aims to seek out the pedagogical functions behind the teacher's decision to code-switch and determine the students' perception towards the teacher's code-switching. The classroom observation and two interview sessions are conducted with one teacher and three participants by applying a case study. It is found that the student's shallow English proficiency influences the student's perception of code-switching, and the teacher is very conscious of the pedagogical functions when she decided to code-switch.